PERANCANGAN WEBSITE PONPES DAN PENGGUNAAN GOOGLE FORM DALAM PEMBELAJARAN SECARA DARING PADA PONDOK PESANTREN AL MUBALIGHIN MUARA BUNGO - Try Susanti; Riri Rahmawati; Elza Efdiningsih; Sepriano, Sepriano (Jurnal Teknik Informatika dan Teknologi Informasi, 2021)
The pandemic that has hit the world has greatly affected the world of education, entering the second semester in 2021 classes are still conducted online and student assignments are sent using online media, namely Whattshap which is only in the form of photos or video tutorials that do not have flashbacks systematically. For this reason, a solution to this problem is needed by creating a google form that allows teachers to ask questions and students can answer directly and teachers can directly check students' homework. With no adequate information system for the delivery of information that can be accessed by everyone who provides information to promote the school. There are two solutions offered at this service, namely as follows: website-based training using web service technology, and online learning using Google Forms. Based on the results of the feedback recapitulation regarding the website and training, there were positive responses given by teachers and TU members, the school website is expected to be able to advance the school and introduce schools to the wider community to be used by the school and the use of Google Forms has made it easier to fill out assignments directly to students and teachers can check assignments immediately so students can directly fill in the form provided